Measurement of quadriceps endurance by fNIRS - (:unkn) unknown (My University, 2006)
In this paper, the changes in muscle deoxygenation trends during a sustained isometric quadriceps (chair squat/half squat) endurance exercise were evaluated among twelve male subjects and the relationship between muscle oxygenation and endurance times was investigated by means of functional near-infrared spectroscopy (fNIRS). Neuromuscular activation and predictions of muscle performance decrements during extended fatiguing task was investigated by means of surface electromyography (sEMG). The results of the study showed that in the subjects who maintained exercise longer than five minutes (group 1), mean Hb recovery time (33 [sec.]) was 37.4% less than the others (group 2, 52.7 [sec.]). Also mean HbO2 decline amplitude (2.53 [a.u.] in group 1 and 2.07 [a.u.] in group 2) and oxy decline amplitude (8.4 [a.u.] in group 1 and 3.04 [a.u.] in group 2) in the beginning of squat exercise are found to be 22.6% and 176.9% bigger in these group. For the EMG parameters, mean slope of MNF and MDF decline are found to be 57.5% and 42.2% bigger in magnitude in group 2 which indicates higher degree of decrement in mean and median frequencies although their mean squat duration time is less. This indicates higher index of fatigue for this group. It is concluded that training leads to altered oxygenation and oxygen extraction capability in the exercising muscle and investigated fNIRS parameters could be used for endurance evaluation.
Keywords: Functional near-infrared spectroscopy (fNIRS); Muscle; Muscular endurance; Surface electromyography (sEMG); Training; Vastus lateralis